Occupational safety and hygiene III selected extended and revised contributions from the International Symposium Occupational Safety and Hygiene, Guimarães, Portugal, 12-13 February 2015 - Arezes, Pedro M.; Baptista, Santos João; Barroso, Mónica P.; Carneiro, Paula; Cordeiro, Patrício; Costa, Nelson; Melo, Rui B.; Miguel, A. Sérgio; Perestrelo, Gonçalo (CRC Press, Taylor & Francis Group, 2015)
The contributions are based on research carried out at universities and other research institutions, and on practical studies developed by Occupational Health & Safety (OHS) practitioners within companies. This book will help to get acquainted with the state-of-the-art within the above mentioned domains, as well as with some practical tools and approaches that are currently used by OHS professionals in a global context.